Pemerintahan Joko Widodo dan Serangan Politik Terhadap KPK - Fariz, Donal (Komisi Pemberantasan Korupsi, 2019)
The result of eradicating corruption is usually parallel with political support from the branches of power. Over the past five years, the Corruption Eradication Commission has been experiencing various political attacks that began with the polemic regarding the selection of candidates for the National Police Chief, the use of Questionnaire Rights by the House of Representatives and the revision of the Corruption Eradication Commission Act. The biggest problem of the KPK also arises from the instability of support from the President for the KPK. Without strong, determined support from the President and the strengthening of political attacks on the KPK, this anti-corruption institution is in an emergency state.